2021
DOI: 10.1101/2021.12.08.471782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Ligands and Transducers on the Neurotensin Receptor 1 (NTS1) Conformational Ensemble

Abstract: Using a discrete, intracellular 19F-NMR probe on Neurotensin receptor 1 (NTS1) transmembrane helix (TM) 6, we aim to understand how ligands and transducers modulate the receptors structural ensemble in solution. For apo NTS1, 19F-NMR spectra reveal an ensemble of at least three states (one inactive and two active-like) in equilibrium that exchange on the ms-s timescale. Dynamic NMR experiments reveal that these substates follow a linear three-site exchange process that is both thermodynamically and kinetically… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 74 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…We sonicated cell pellets containing enNTS1(Q301 6.28 /C172S . 16 Intact and protease-digested LC-MS confirmed that 19 F-enNTS1(Q301C 6.28 /C172S 3.55 ) was exclusively-labeled at Q301C 6.28 with no observable unreacted 19 F-BTFMA [Fig. 3(C) and Table S1].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…We sonicated cell pellets containing enNTS1(Q301 6.28 /C172S . 16 Intact and protease-digested LC-MS confirmed that 19 F-enNTS1(Q301C 6.28 /C172S 3.55 ) was exclusively-labeled at Q301C 6.28 with no observable unreacted 19 F-BTFMA [Fig. 3(C) and Table S1].…”
Section: Resultsmentioning
confidence: 95%
“…no offsite labeling). 9,13,16 As a negative control, we engineered 19 F-enNTS1(Q301 6.28 /C172S 3.55 ) with residue 301 reverted to glutamine and repeated the experiment. The spectrum contained two resonances that were present in the 19 F-enNTS1(Q301C 6.28 /C172S 3.55 ) spectrum indicative of offsite labeling [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations